Analysis of Stress Levels in Final Semester Students of the Department of Sports Education and Coaching at Jambi University (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine how many final-year students in the Department of Sports and Coaching at Jambi University experience stress while completing their final assignments (thesis). The method used is a quantitative descriptive method and a questionnaire. The population used was all 196 students of the 2021 intake of the Department of Sports and Health Education at Jambi University, consisting of 141 students majoring in Sports and Health Education and 55 students majoring in Sports Coaching. The study sample used a total sampling with a total sample of 196 samples. The data collection techniques used were questionnaires, observation, and documentation. And data analysis techniques used were validity, reliability, and percentage. The results of the analysis concluded that the stress levels of final-semester students in the Department of Sports Education and Coaching at Jambi University were in the mild (51%) and moderate (49%) categories. No students fell into the severe stress category (0%), so it can be concluded that the majority of students are still able to manage the pressure they face.